Growth of clones of Hevea brasiliensis (Willd. ex A.Juss.) Müll.Arg. in juvenile stage established in clonal fields, Meta, Colombia - Sandra Liliana Castañeda-Garzón; Franck Rivano; Argenis Antonio Mora Garcés (Temas Agrarios, 2024)
Hevea brasiliensis is the greatest source of natural rubber and raw material in several industrial products manufacture. In Colombia, it has been commercially established in five productive units; however, the genetic basis is limited and foliar diseases have influenced the development and the production. In La Libertad Research Center (Villavicencio) and Taluma Experimental Field (Puerto López) of the Corporación Colombiana de Investigación Agropecuaria – AGROSAVIA, clonal trials, at small-scale and large-scale, were established to evaluate the performance assessment, associated with growth, of seven clones from CIRAD-Michelin. Selection Collection series CDC, FDR, MDF y PMB, and FX 3864 and RRIM 600 as well. In juvenile stage, the trunk circumference (CIRC) was measured every six months, and the annual increase average (IMA-CIRC) was calculated. Variance analysis and means comparison were carried out. At eight years of age, the FDR 5788 clone showed IMA-CIRC of 8.20 cm year-1 and 6.87 cm year-1 in La Libertad and Taluma, respectively; differences in growth between clones were observed. In the Piedemonte llanero (La Libertad), the FDR 5788 and RRIM 600 clones were notable for their growth, whereas in the Altilllanura (Puerto López) PMB 1 and FDR 5788 were remarkable. In La Libertad, the FDR 5788, RRIM 600 and CDC 312 clones exceeded the CIRC of 50 cm at sixth year, in contrast to Taluma, where it occurred at seventh year for PMB1 and DFR 5788.